The Insight of Learning English Letters and Numbers on Youtube of Four Years Old Children - Misli. A; Yusniati N. Sabata; Sitti Hardianti (English Education Study Program, 2022)
Currently, in the era of advanced technological development, children have used YouTube in their daily lives. YouTube is a site that contains various kinds of videos, ranging from movies, music, TV series and so on that can be found on YouTube. Therefore, this research aims to find out the benefit of youtube for learning numbers and letters by four years old children and to find the challenges of youtube for learning numbers and letters by four years old children. This research is qualitative research. The research subject were three children and three parents. This research was also conducted at Bonebalantak. Researcher used two instruments in finding the data they are observation and interview. From the results it is found that the benefits of youtube are a source of new knowledge for children in learning English numbers and letters and youtube helps parents in teaching numbers and letters to children, the challenge is to cause addiction in watching youtube for children and children watching videos that not age appropriate. the conclusion of this research is that the insights to learning english letters and numbers in four year old children can be obtained by using youtube, youtube provides knowledge for children in learning numbers and letters in english, besides that youtube also has challenges in using it but it can be solved.